The Effect of Outbound Brand Syariah and Social Media Marketing on Purchase Interest of BSI Auction Assets with Public Trust as an Intervening Variable - Pradnawati, Eriza; Nurhidayah, Nurhidayah; Alrasyid, Harun (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2025)
This study aims to analyze the influence of outbound sharia brand and social media marketing on public trust, analyze the influence of outbound sharia brand and social media marketing on interest in purchasing auction assets, analyze the influence of public trust on interest in purchasing auction assets, and analyze the influence of outbound sharia brand and social media marketing on interest in purchasing auction assets through public trust. The number of samples in this study involved 200 customers. The analysis technique used SmartPLS. The results of the analysis show that outbound sharia brand influences public trust. Social media marketing influences public trust. Outbound sharia brand influences interest in purchasing auction assets. Social media marketing influences interest in purchasing auction assets. Public trust influences interest in purchasing auction assets. Outbound sharia brand influences interest in purchasing auction assets through public trust. Social media marketing influences interest in purchasing auction assets through public trust.